Primordial Germ Cells: Current Knowledge and Perspectives - Aleksandar Nikolic; Vladislav Volarevic; Lyle Armstrong; Majlinda Lako; Miodrag Stojkovic (Stem Cells International)
Infertility is a condition that occurs very frequently and understanding what defines normal fertility is crucial to helping patients. Causes of infertility are numerous and the treatment often does not lead to desired pregnancy especially when there is a lack of functional gametes. In humans, the primordial germ cell (PGC) is the primary undifferentiated stem cell type that will differentiate towards gametes: spermatozoa or oocytes. With the development of stem cell biology and differentiation protocols, PGC can be obtained from pluripotent stem cells providing a new therapeutic possibility to treat infertile couples. Recent studies demonstrated that viable mouse pups could be obtained from in vitro differentiated stem cells suggesting that translation of these results to human is closer. Therefore, the aim of this review is to summarize current knowledge about PGC indicating the perspective of their use in both research and medical application for the treatment of infertility.